Inlet and outlet chemical analyses at Lake Erken, 2000-2016 - Inlet and outlet chemical analyses at Lake Erken 2000-2011 - Yang, Yang (Uppsala University, 2018)
Data from inlet and outlet chemical analyses at Lake Erken 2000-2016, colected by The Erken laboratory.
Variables: pH/Conductivity/ Turbidity/ Alkalinity/ Absorbance/ particles/ Chla/ Temperature/ nutrients

The Erken laboratory is located by the shore of lake Erken, 70 km northeast of Stockholm. A substantial lake measurement program has been running for the last 30 years, which includes manual sampling along with high frequency automatic measurements.

Inlet and outlet chemical analyses at Lake Erken 2000-2011
pH/Conductivity/ Turbidity/ Alkalinity/ Absorbance/ particles/ Chla/ Temperature/ nutrients

The data is free to use, but please inform us, so that we can keep track about the projects that make use of our data.

Data från inlopps- och utloppskemiska analyser vid sjön Erken 2000-2016, utförda av Erkens monitoringprogram.
Innehåller bland annat variabler för: temperatur, pH, konduktivitet, alkalinitet, grumlighet, absorbans, suspenderat material, fosfatfosfor, syrgas.

Erkenlaboratoriet är belägen vid stranden av sjön Erken, 70 km nordost om Stockholm. Stationen bedriver sedan ungefär 30 år tillbaka ett omfattande miljöövervakningsprogram av sjön Erken, som inkluderar manuella mätningar och högfrekventa automatiska mätningar.

Inlopps- och utloppskemiska analyser vid sjön Erken 2000-2011
Innehåller bland annat variabler för: temperatur, pH, konduktivitet, alkalinitet, grumlighet, absorbans, suspenderat material, fosfatfosfor, syrgas.

Det är fritt fram att använda data från vårt monitoringprogram, men vi vill att ni som använder datat ska informera oss så att vi kan hålla reda på vilka projekt som utnyttjar Erkens monitoringprogram.
Inlopps- och utloppskemiska analyser vid sjön Erken, 2000-2016 - Inlopps- och utloppskemiska analyser vid sjön Erken 2000-2011
Keywords: LAKE/POND; RIVERS/STREAM; Environmental Sciences; Miljövetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser